FAKTOR-FAKTOR YANG MEMPENGARUHI PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) PADA DINAS PERTANIAN PROVINSI MALUKU - Mohammad Syafaat Warandi (Politeknik Negeri Ambon, 2025)
Introduction: This study aims to determine the effect of building leasing, land leasing, seed certification, sale of tillers, sale of eggs and sale of livestock on increasing PAD in the Agriculture Service of Maluku Province. Methods: The sample in this study is income data from the Maluku province agriculture service. Secondary data collection is by looking at the Maluku provincial agriculture service PAD receipts from 2020 to 2024. The analysis technique used is SPSS version 22.Results: Based on the results of the research conducted, it can be concluded that building rental has an effect on increasing PAD, land leasing has an effect on increasing PAD, seed certification has an effect on increasing PAD, sales of chicks has an effect on increasing PAD, egg sales has an effect on increasing PAD and livestock sales has an effect on increasing PAD. Keywords: Building rental, land rental, seed certification, sale of tillers, sale of livestock, increase of PAD